2020
DOI: 10.1038/s41598-020-69429-6
|View full text |Cite
|
Sign up to set email alerts
|

EGCG impedes human Tau aggregation and interacts with Tau

Abstract: Tau aggregation and accumulation is a key event in the pathogenesis of Alzheimer's disease. Inhibition of Tau aggregation is therefore a potential therapeutic strategy to ameliorate the disease. Phytochemicals are being highlighted as potential aggregation inhibitors. Epigallocatechin-3-gallate (EGCG) is an active phytochemical of green tea that has shown its potency against various diseases including aggregation inhibition of repeat Tau. The potency of EGCG in altering the PHF assembly of full-length human Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 61 publications
2
36
0
Order By: Relevance
“…At the molecular level, auto-oxidized EGCG reacts with free primary amine groups of proteins, forms a Schiff base, and induces fibril remodeling [ 37 , 38 ]. Interestingly, this mechanism not only might be operative with Aβ and TAU [ 39 ] in AD but also to other neurodegenerative disorders such as α-synuclein (in Parkinson’s disease), Huntingtin protein (in Huntington’s disease), and islet amyloid polypeptide (IAPP, amylin) in the pancreas most probably through a common mechanism, in which EGCG binds to cross-beta sheets amyloid aggregation intermediates remodeling the oligomeric amyloid or pre-formed amyloid fibrils into non-amyloidogenic species [ 21 , 40 ]. According to this view, we found that EGCG significantly reduces (i)sAPPβf aggregates in PSEN 1 E280A ChLNs demonstrated by FM staining, and FC analysis.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, auto-oxidized EGCG reacts with free primary amine groups of proteins, forms a Schiff base, and induces fibril remodeling [ 37 , 38 ]. Interestingly, this mechanism not only might be operative with Aβ and TAU [ 39 ] in AD but also to other neurodegenerative disorders such as α-synuclein (in Parkinson’s disease), Huntingtin protein (in Huntington’s disease), and islet amyloid polypeptide (IAPP, amylin) in the pancreas most probably through a common mechanism, in which EGCG binds to cross-beta sheets amyloid aggregation intermediates remodeling the oligomeric amyloid or pre-formed amyloid fibrils into non-amyloidogenic species [ 21 , 40 ]. According to this view, we found that EGCG significantly reduces (i)sAPPβf aggregates in PSEN 1 E280A ChLNs demonstrated by FM staining, and FC analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of oligomers and aggregates were observed by TEM by spotting it onto 400 mesh carbon‐coated copper grids and stained with 2% uranyl acetate. The grids were dried and analyzed by Tecnai T20 at 120 kV for TEM study 82 . Tau oligomers and aggregates were spotted onto a nitrocellulose membrane at a final concentration of 2.5 mg/mL and allowed for complete drying.…”
Section: Methodsmentioning
confidence: 99%
“…This effect was characterized in a study conducted in 2015, which combined cell-free aggregation and a cell-based assay, and found that EGCG could be a potent inhibitor of tau aggregation and toxicity, preventing the aggregation of tau protein into toxic oligomers at substoichiometric ratios [150]. More recently, a study with various biophysical and biochemical analyses suggested a possible dual effect of EGCG on aggregation inhibition and disassembly of full-length tau and their binding affinity [28].…”
Section: Egcg Targeting Misfolded Aggregates In Ad and Pdmentioning
confidence: 99%
“…Studies have revealed that EGCG can interact with a variety of proteins linked to protein misfolding, such as Aβ, tau, α-synuclein (α-syn), transthyretin (TTR), and huntingtin [25][26][27][28]. This review addresses the contribution of EGCG research toward advances in neurodegenerative disease drug discovery.…”
Section: Introductionmentioning
confidence: 99%